Laser Therapy and Stroke: Quantification of Methodological Requirements in Consideration of Yellow Laser - Daniela Litscher; Gerhard Litscher (International Journal of Photoenergy)
Every year more than 600,000 Europeans suffer a stroke. This burdens the health system and it can be assumed that the incidence of stroke will increase in the coming decades. In addition to conventional methods of drug therapy, stroke is sometimes treated with highly invasive methods. The non-invasive laser procedures on the other hand operate through the bony skull. Large-scale laser studies are being conducted with varying degrees of success around the world, and without the certainty that the corresponding laser beam even penetrates the bone. No one currently knows in detail the laser parameters that have to be chosen on the intact skull; so that the laser light can develop its possible efficacy inside the human skull. The present study demonstrates that the values for the wavelengths 810 nm and 658 nm correlate well with previous experimental findings however the information on the yellow laser was estimated incorrectly by a factor of ten by other authors. Further research on the topic is important so that one can be sure to apply the correct wavelength and parameters. This can open up new dimensions in transcranial laser therapy, not only in stroke patients.